The sovereign self aesthetic autonomy from the Enlightenment to the avant-garde - Kester, Grant H. 1959- (Duke University Press, 2023)
"The Sovereign Self explores the complex history of artistic subjectivity and the principle of autonomy that it exemplifies. Grant H. Kester argues that the modern artistic self is the basis for a whole series of subsequent institutional and discursive enclosures which are understood to be uniquely free from the forms of ideological domination that constrain all other forms of cultural production. Moreover, he explores how the question of aesthetic autonomy has ramifications that extend well beyond art to larger issues associated with the nature of political transformation, including the complex relations between the artistic avant-garde and the revolutionary vanguard. In order to explore these issues, Kester considers the evolving discourse of aesthetic autonomy throughout history, from its origins in Enlightenment aesthetic philosophy, through the initial emergence of avant-garde art movements in the nineteenth century, to its more contemporary manifestation in the neo-avant-garde of the 1970s"--
Includes bibliographical references and index
Keywords: Ästhetik; Autonomie; Künstler; Art / Philosophy; Art criticism; Autonomy (Psychology) in art; Subjectivity in art; Avant-garde (Aesthetics) / History / 20th century; Art, Modern / Political aspects; Art and society / History / 20th century; ART / Criticism & Theory; ART / History / Contemporary (1945-)